Utilization of low cost adipose tissue waste as a source of stearic acid for use in rubber activation - Guyo, Upenyu; Zinyama, Ngceboyakwethu; Sebata, Edith (2016)
Stearic acid was extracted from adipose tissue which was obtained from a waste heap from a local tannery. The waste adipose tissue was prepared for use by cutting, mixing, cleaning and refrigeration. By solvent extraction using methyl ether, a solid fat was obtained which was then hydrolyzed using water at 60oC and heterogeneous catalyst stones of calcium and magnesium oxide. Chemical characterization of stearic acid white flakes for parameters such as the melting point, specific gravity, iodine value, acid value and copper and manganese content was performed. A fatty acid yield of 68% was obtained. The iodine value of 10.02 and the melting point of 50.3 oC show a reasonable degree of saturation and stability. A high level of 198.89 acid value was obtained. The absence of copper and manganese, content which were determined qualitatively, indicates the suitability of the extracted stearic acid for rubber compounding without being a catalyst of ageing. Its specific gravity of 0.8533 indicates its lightness in respect to rubber compounding. Physical tests on the rubber compounded with the stearic acid were performed according to SATRA standards for general product safety. Simulated vulcanization tests on the rheometer were within 2 minutes, which is suggestive of activation. The rubber had a tensile strength of 6.527 x 103, abrasion resistance of 0.96 and hardness of 75, which are all indicative of a good service life of rubber compounded with the stearic acid.